ANALISIS PENGUKURAN KINERJA RUMAH SAKIT DENGAN PENERAPAN METODE BALANCED SCORECARD (Studi Kasus Pada RSUD â€œKanjuruhanâ€ Kepanjen Kabupaten Malang) - Anisak, Laila Yulita; Affandy, Didied Poernawan (Jurnal Ilmiah Mahasiswa FEB, 2014)
The purpose of this research is to measure performanceÂ  RSUD â€œKanjuruhanâ€ Kepanjen Kabupaten MalangÂ  by using the conceptÂ  Balanced Scorecards referring to four perspectiveÂ  whichÂ  are, customersÂ  perspective, financial perspective, internal business process perspective, and also growth and learningÂ  perspective.Â  The research used descriptive method by using secondary data among years of 2010 â€“ 2012 and primary data to measure employees and patients satisfaction The results showed that the performance of RSUD "Kanjuruhan" Malang Kepanjen measured using Balanced Scorecard overall can be concluded to be "adequateâ€. The results can be seen in every perspective, which perspective of the customer onÂ  the customerÂ  satisfactionÂ  indicatorÂ  shows â€œsatisfiedâ€result withÂ  the amount of 13560, the indicator of customer retention shows fluctuative result from year 2010 increased by 44 % to 49 % in 2011, while in 2012 decreased to 45 %, on customer acquisition indicators also showed fluctuative result that declined from 56 % in 2010 to 51 % in 2011, while the year 2012 increased to 55%. In financial perspective for the economic ratio showed â€œfairly economicalâ€Â  result, efficiency ratioÂ  in 2010Â  showed â€œefficientâ€ result, butÂ  in 2011 and 2012 showed that the result are â€œnot efficientâ€, while the ratio of the effectiveness in RSUD "Kanjuruhan" Kepanjen Malang was ableÂ  to be â€œeffectiveâ€,Â  itÂ  is evidencedÂ  from the achievement of revenue budget has been made. In internal business process perspective (BOR, TOI, BTO, ALOS, GDR, NDR) as a whole was rated "adequate". In the learning and growth perspective on employee satisfaction indicator shows the results for 8461, whichÂ  meansÂ  employeesÂ  feelÂ  â€œrather satisfiedâ€, on employee retention indicator show â€œadequateâ€ results, while the productivity of the employees showed â€œpoorâ€ result. This is evidenced by the increasing percentage of employee absences are reflected in employee productivity indicators. Keywords: Measuring Performance, Hospital, Balanced Scorecard.